Factors associated with burden of caring in Huntington’s disease - Md Rosli, Najwa Hanim; Loi, Samantha M; Mangelsdorf, Simone; Farrand, Sarah; Eratne, Dhamidhu; Velakoulis, Dennis (2018)
Huntington’s disease (HD) is an inherited progressive neurodegenerative disorder which affects motor function, cognition and the psychological state of HD patients. Its triad of unique symptoms compared to other neurodegenerative disorders might give rise to a higher level of burden for their carers. Aims: The aim of this study was to explore factors associated with the burden of caring in patients with HD. Methods: Eighty-one HD patients and their carers participated in this study. Motor disturbances was assessed using the Unified Huntington’s Disease Rating Scale (UHDRS) motor scale, cognitive impairment was assessed with the Neuropsychiatry Unit Cognitive Assessment Tool (NUCOG), psychological status of both patient and carer were assessed using the Depression Anxiety Stress scale (DASS21), behavior of the patient was assessed with Revised Cambridge Behavioural Inventory (CBI-r) and carer burden was assessed with Zarit Burden Interview (ZBI). Results: Motor disturbances, attention and executive domains of cognition, psychological state of carers and patient’s behavior disturbances were found to affect burden of care in this study. Conclusion: HD has a major impact on carers. These findings highlight the needs for these factors to be targeted in order to reduce the burden among carer in HD.